Modus Operandi Penipuan Online Melalui Aplikasi Shopee Pay Later (Nomor Perkara: LP/B-35/II/2025/SPKT Studi Kasus Di Wilayah Hukum Kepolisian Daerah Jambi) - Riyan Febiyan; Suzanalisa Suzanalisa; Sarbaini Sarbaini (Legalitas: Jurnal Hukum, 2026)
Advancements in information technology have brought about significant changes in our lives; notably, this technology enables people to purchase goods more easily than ever before. This study aims to examine the law enforcement actions taken by the Jambi Regional Police against perpetrators of online fraud involving the Shopee PayLater service, the obstacles encountered during such enforcement, and the measures the Jambi Regional Police can implement to overcome these challenges. This is an empirical study. The findings indicate that the Jambi Regional Police have conducted law enforcement actions based on sufficient evidence, establishing that the suspects met the elements of criminal offenses as stipulated in Articles 378, 379a, and 372 of the Criminal Code (KUHP). However, these enforcement efforts face various obstacles, including the absence of specific regulations regarding the misuse of "paylater" services, difficulties in establishing electronic evidence, a shortage of personnel with expertise in cybercrime, and coordination challenges with digital platform providers. Furthermore, low levels of digital literacy and public legal awareness exacerbate the risk of fraud. To address these obstacles, the Jambi Regional Police need to undertake strategic measures, such as formulating specific Standard Operating Procedures (SOPs), enhancing investigator capacity through cybercrime training, optimizing digital forensic facilities, and strengthening cross-sector cooperation.